KaJian Peranan ASDP Merak Dalam Mendukung Pengembangan Angkutan Logistik Nasional - Mutholib, Abdul (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2011)
Merak harbor crossing is one of the infrastructure that serves 80 percent of Indonesia's economy in the island of Java and Sumatra. Merak harbor crossings currently has 5 dock supported by a fruit terminal with an area of 8260 m2 bus that can accommodate 330 buses. In addition there is also a parking lot to accommodate vehicles waiting to enter the vessel with an area of 18 ha can accommodate 752 vehicles. Based on data obtained from the office of the Administrator port of Bantam, Over the past three consecutive years ie 2007 - 2009. respectively in 2007 transported 6, 8 million tons of goods, in 2008 transported 5. 7 million tons while for the year 2009 rose to 7.2 million tonnes. The increasing demand for transportation services of PT Indonesia Ferry crossings as a port operator plans to cooperate with the municipal government to build the dock VI Cilegon near the area of Integrated Terminal Peacock (ITM). The plan is dedicated dock for passengers pedestrians. VI Pier development project is planned to be conducted early 2011